Interview mit Hagen Keller - Guglielmotti, Paola; Isabella, Giovanni; Lazzari, Tiziana; Varanini, Gian Maria (Reti Medievali Rivista, 2008)
The first part of this interview addresses the cultural, social and political milieu that shaped Hagen Keller’s education in Germany, the relations with both his mentor Gerd Tellenbach and the other scholars; the approach to prosopography to understand the power structures. Then the interview examines the Roman experience in the Sixties (a scientific and also human one); the book Adelsherrschaft und ständische Gesellschaft and the debate that has attracted; the relationship between local history, regional history and general history; the Ottonian dynasty, the pragmatic use of writing and the symbolic communication; and finally how research is organized and evalueted in Germany.